Effects of fly ash and dolomite powder on the properties of self-compacting concrete - Barbhuiya, Salim (Elsevier BV, 2011)
Fly ash and limestone powder are found to be the traditional materials to be used in controlling the segregation potential and deformability of fresh SCC. This research deals with the utilisation of an alternative material, dolomite powder, instead of limestone powder, for the production of SCC. Test results indicated that it is possible to manufacture SCC using fly ash and dolomite powder. The mix containing fly ash and dolomite powder in the ratio 3:1 was found to satisfy the requirements suggested by the European Federation of Producers and Contractors of Specialist Products for Structures (EFNARC) guide for making SCC. © 2011 Elsevier Ltd. All rights reserved.